Revised Filter Profiles and Zero Points for Broadband Photometry. (4th January 2016) - Mann, Andrew W.; von Braun, Kaspar
Abstract: Estimating accurate bolometric fluxes for stars requires reliable photometry to absolutely flux calibrate the spectra. This is a significant problem for studies of very bright stars, which are generally saturated in modern photometric surveys. Instead we must rely on photometry with less precise calibration. We utilize precisely flux-calibrated spectra to derive improved filter bandpasses and zero points for the most common sources of photometry for bright stars. In total, we test 39 different filters in the General Catalog of Photometric Data as well as those from Tycho-2 and Hipparcos . We show that utilizing inaccurate filter profiles from the literature can create significant color terms resulting in fluxes that deviate by ≳10% from actual values. To remedy this we employ an empirical approach; we iteratively adjust the literature filter profile and zero point, convolve it with catalog spectra, and compare to the corresponding flux from the photometry. We adopt the passband values that produce the best agreement between photometry and spectroscopy and are independent of stellar color. We find that while most zero points change by < 5%, a few systems change by 10-15%. Our final profiles and zero points are similar to recent estimates from the literature. Based on determinations of systematic errors in our selected spectroscopic libraries, we estimate that most of our improved zero points are accurate to 0.5-1%.